Neonatal exchange transfusion for hyperbilirubinemia in Guilan (the north province of Iran): a 3-year experience - Esfandiarpour, Bahareh; Ebrahimi, Hannan; Karkan, Morteza Fallah; Farahmand, Nastaran; Karambin, Mohammad Mehdi (The Turkish Journal of Pediatrics, 2012)
Exchange transfusion is the standard method for treatment of severe hyperbilirubinemia. Our goal was to determine the indications for exchange transfusion (ECT) and the rates of ECT-related adverse events. A retrospective descriptive investigation was performed in newborns that underwent ECT at 17 Shahrivar Pediatric Hospital, Rasht, Guilan province during the period April 2008 to April 2011. Of the 69 patients, 2 (2.9%) required more than one ECT. The mean total serum bilirubin before ECT was 21.55 ± 5.12 mg/dl. The most common cause of ECT was ABO incompatibility (26.1%). ECT complications occurred in 9 neonates (13.0%), the most common being sepsis (7.4%). No case of ECT related mortality was observed. All the adverse events resolved completely before discharge. ABO isoimmunization was the most common cause of ECT in this study. The majority of adverse events associated with ECT are asymptomatic and reversible.